Early-onset emphysema in a large French-Canadian family: a genetic investigation. Issue 5 (May 2019) - Bossé, Yohan; Lamontagne, Maxime; Gaudreault, Nathalie; Racine, Christine; Levesque, Marie-Hélène; Smith, Benjamin M; Auger, Dominique; Clemenceau, Alisson; Paré, Marie-Ève; Laviolette, Louis; Tremblay, Victor; Maranda, Bruno; et al.
Summary: Background: Inherited mutations in SERPINA1 coding for the alpha-1 antitrypsin (A1AT) protein is the only well established cause of hereditary emphysema. We aimed to identify the genetic ecause of early-onset emphysema in a five-generation French-Canadian family free of A1AT deficiency. Methods: Between Dec 1, 2014, and April 1, 2017, we investigated 63 individuals from a single pedigree, including 55 with DNA available. Whole-exome sequencing was done in a convenience sample of 14 individuals (nine with unambiguous expression of the typical form of emphysema observed in this family). We filtered rare non-synonymous variants that were predicted to be damaging to identify a single mutation in a biologically relevant gene shared among all affected individuals. We assessed segregation with the disease in additional family members who were not evaluated by whole-exome sequencing. The effect of the candidate variant on protein function was evaluated in vitro. mRNA and protein expression of the candidate gene was assessed in lung samples from unrelated individuals (n=80) with and without emphysema who underwent surgery for lung cancer at our institution. Findings: A rare in-silico-predicted damaging variant (Ala455Thr) was identified in the protein tyrosine phosphatase non-receptor type 6 ( PTPN6 ) gene, also known as SHP-1, an important negative regulator of immune processes. 20 (95%) of 21 family members with computed tomography-confirmed emphysema were heterozygotes for the Ala455Thr mutation. No Thr455 homozygotes were identified. Emphysema or reduced diffusion capacity was observed in all heterozygotes with a history of smoking. Incomplete penetrance of the mutation and variable degrees of emphysema were observed in never smokers. The Ala455Thr mutation in SHP-1 caused a reduction in phosphatase activity in vitro, confirming the loss-of-function effect of the mutation. mRNA and protein expression of PTPN6 were upregulated in smokers, but were not associated with emphysema or severity of airflow limitation. Interpretation: An inherited variant in the gene PTPN6 is responsible for early-onset emphysema in this family. To our knowledge, this is the second form of hereditary emphysema since the discovery of A1AT deficiency in the 1960s, representing a breakthrough in understanding the genetics and pathogenesis of emphysema. Funding: Fonds sur les maladies respiratoires J.-D. Bégin–P.-H. Lavoie de l'Université Laval, Fondation de l'Institut universitaire de cardiologie et de pneumologie de Québec, CIHR/GSK research Chair on COPD at Université Laval, and the Canadian Institutes of Health Research.